Palaeolclimatic significance of palynological assemblages from the Siwalik sediments in the Dudhaura Khola section, central Nepal (Journal of Nepal Geological Society, 2013)
The palynological study of the Rapti Formation and Amlekhganj Formation from the Siwalik Group in the Dudhaura Khola section revealed plethora of information to interpret the past vegetation and climate existed during Late Miocene in the southern margin of the Nepal Himalaya. Altogether 30 samples were collected from Rapti Formation and Amlekhganj Formations exposed in the Dudhaura Khola section for the palynological study. Palynological assemblages recovered from the upper part of Rapti Formation and lower part of Amlekhganj Formation consist of 5 families and 10 genera from monocotyledon, 8 families and 14 genera from dicotyledon, 1 family and 4 genera from Gymnosperm and 5 families from Pteridophytes. High presence of Palm pollen and Ceratopteris spores in the Rapti Formation and Amlekhganj Formation suggests that the climate was warm and humid. The riverine vegetation is documented by the presence of Alnus, Typha, Potamogeton, Liliaceae and Poaceae.The frequency of zygnemataceous spores is common in the Rapti Formation while it is decreases towards the bottom part of the Amlekhganj Formation. There is little gymnosperm pollen in the Amlekhganj Formation but their frequency and distribution is very less. This suggests change of vegetation pattern from tropical-subtropical forest to lower temperate forest during the deposition of Amlekhganj Formation and after wards.